Hyperia Sdn Bhd / Nor Azam Azram Md Nordin... [et al.] - Md Nordin, Nor Azam Azram; Mohd Fadzli, Mohd Hilmie; Mohd Jamil, Mohd Fadzhill; Majid, Shaiful Johari; Yahya, Mohd Sahffuan (2000)
Hyperia Sdn Bhd is a company or business that produce the product start from producer direct to retailer. Operation planning is an important planning in order to be success one’s activities that have been planned. Their company is formed to reach government exclamation to get more local entrepreneur participate in business. Hyperia Sdn Bhd is only an infant (that is new organization) that exists in this cake and confectionery field. This business operates in Mergong Industrial area which is Alor Setar, Kedah.